Characterization of gene expression alterations in β-catenin activated Huh7 hepatocarcinoma cell lines by construction and verification of a sage library - Çavuşoğlu, Kader. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
β-catenin, a cytoplasmic component of the Wnt signaling pathway, is observed to be aberrantly activated in several types of tumors, including hepatocellular carcinoma. The aim of this study is to identify novel genes that are regulated by active β-catenin/TCF signaling in hepatocellular carcinoma cell line Huh7 and to investigate their relationship with cell growth control. SAGE libraries from Huh7-derived cells with high and low β-catenin/TCF activities were constructed and 431 differentially expressed genes were identified; 329 of them showed decreased expression profile in high activity cells, whereas the remaining 102 tags showed increase. Transient overexpression of β-catenin resulted in down regulation of mRNA expression levels of two of these genes, Gene 3 and Gene 6. Gene 6 was also analysed for the possible role in cell growth control and a significant effect on Huh7 proliferation was observed. Our findings suggest two novel candidate targets of Wnt/β-catenin pathway in hepatocellular carcinoma cell line Huh7 whose direct interaction with β-catenin/Tcf complex should be further analysed. One of these genes, Gene 6 might play a role in cell growth control.
Keywords: Wnt genes.; Liver -- Cancer.